United Nations: confronting the challenges of a global society - "Krasno,Jean E.(ed.)" (New Delhi, 2005)
Despite the high visibility of the United Nations in various peacekeeping operations, the enormous role that it plays in the global arena goes largely unnoticed. This new book focuses on that larger role, bringing to life the evolutionary process of multilateral interaction that is the foundation of the organization, the sometimes heated politics behind its operations, and the key personalities who have shaped it. The authors move from the creation of the UN to the present debates about reform. Their discussion of UN activities in the areas of human rights, elections, development, disarmament, and peacekeeping as well as procedures offers an accessible introduction to a complex, critical subject.
Keywords: United Nations